From Risk to Uncertainty: A Systematic Literature Review of Business Decision-Making in the Era of Global Business Transformation - I Made Surya Negara Sudirman (The Journal of Financial, Accounting, and Economics, 2026)
Changes in the global business environment influenced by digital transformation, geopolitical dynamics, climate change, and increasing economic complexity have made risk and uncertainty strategic issues in business decision-making. Although these two concepts are often used interchangeably, the literature shows that risk is a condition whose probability can still be estimated, while uncertainty relates to limited information that makes the probability and consequences of an event difficult to predict. This conceptual difference has significant implications for the effectiveness of organizational decision-making, especially in dynamic business environments. This study aims to synthesize the development of literature on the concepts of risk and uncertainty in business decision-making, identify research trends, evaluate theoretical and practical contributions, and identify research gaps that remain open during the period 2015–2025. The study employed a Systematic Literature Review (SLR) approach, adhering to the PRISMA 2020 guidelines. The literature search was conducted through five academic databases: Scopus, ScienceDirect, SpringerLink, Wiley Online Library, and Google Scholar. Of the 18 identified articles, nine met all inclusion criteria and were analyzed using content analysis and thematic synthesis. The results indicate that the literature is evolving toward a more integrative risk management paradigm through the application of Enterprise Risk Management (ERM), digital transformation, artificial intelligence, data analytics, and a sustainability approach (Environmental, Social, and Governance/ESG). The study also identified that the implementation of risk and uncertainty concepts in MSMEs and organizations in developing countries is still relatively limited, thus opening opportunities for further research that integrates behavioral, technological, and local characteristics in developing more adaptive and resilient business decision-making models.